Reply to comment by P. Foukal on “A homogeneous database of sunspot areas covering more than 130 years” - Balmaceda, Laura Antonia (2010)
Fil: Balmaceda, Laura Antonia. Consejo Nacional de Investigaciones Cientificas y Tecnicas. Centro Cientifico Tecnologico San Juan. Instituto de Ciencias Astronomicas de la Tierra y del Espacio; Argentina